Highly Conductive P-Type MAPbI3 Films and Crystals via Sodium Doping - Li, Yujiao; Li, Chen; Yu, Huanqin; Yuan, Beilei; Xu, Fan; Wei, Haoming; Cao, Bingqiang (Frontiers in Chemistry, 2020)
To regulate the optical and electrical properties of the intrinsic methylammonium lead iodide (CH3NH3PbI3) crystals and films, we dope them with sodium (Na) by selecting sodium iodide (NaI) as dopant source. The highly conductive p-type sodium-doped CH3NH3PbI3 (MAPbI3: Na) perovskite single crystals and thin films are successfully grown by inverse temperature crystallization (ITC) method and antisolvent spin-coating (ASC) method, respectively. With the increase of Na+ doping concentration, the grain size of the film increases, the surface becomes smoother and the crystallinity improves. Hall effect results demonstrate that both the MAPbI3: Na thin films and single crystals change its quasi-insulating intrinsic conductivity to highly conductive p-type conductivity. The room-temperature photoluminescence (PL) peaks of doped MAPbI3 films slightly blue shift, while the photocarriers lifetime becomes longer. The optical fingerprints of the doped levels in MAPbI3: Na perovskites can be identified by temperature-dependent PL. Obvious fingerprints of Na-related acceptor (A0X) levels in the doped MAPbI3: Na were observed at 10 K. These results suggest that sodium doping is an effective way to grow highly conductive p-type MAPbI3 perovskites.